Exoskeleton Intervention in Car Assembly Line to Minimize the Potential of Musculoskeletal Disorder Risk - Chedana, Saskara B'tari; Redi, Anak Agung Ngurah Perwira; Darma, Panji Nursetia (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2026)
Musculoskeletal Disorders (MSDs) remain one of the most prevalent occupational health issues worldwide, commonly caused by repetitive motions, awkward postures, and excessive physical load. In Indonesia, more than 40% of workers from various industries report MSD symptoms. Although ergonomic control measures aligned with international standards (e.g. ISO) have been implemented, these strategies are often insufficient to ensure safer postures sustained during work activities. Exoskeletons have been developed as a promising supplemental ergonomic intervention through its biomechanical mechanisms. This study examined the effectiveness of a passive shoulder-support exoskeleton adoption in one of the car assembly activities. Ten young adults performed repetitive bolt-tightening under two conditions: with and without exoskeleton assistance. MSD symptoms were assessed using the Borg CR-10 exertion scale, while postural risk was evaluated using the Rapid Upper Limb Assessment (RULA). Additionally, task completion and recovery times were recorded to evaluate task efficiency. Subjective perception regarding acceptability and safety perception towards the device were assessed through a questionnaire. Based on the experimental results, the exoskeleton reduced perceived muscle exertion mainly in the wrist region and reduced task completion time by 13.6%. A notable reduction in post-task recovery time (19.08%) was also observed under the exoskeleton condition. The overall RULA score decreased from 7 (high risk) to 5.5 (medium risk), indicating a reduction in ergonomic risk. Furthermore, questionnaire responses revealed positive perceptions related to task speed and mobility support, although some usability challenges were noted. Overall, these findings suggest that passive shoulder-support exoskeletons have the potential to enhance worker safety, comfort, and task efficiency in repetitive elevated automotive assembly tasks.